The effect of physical exercise on cardiopulmonary fitness in burn patients: A meta-analysis - Da Huang; XiaoXiang Wan; Juan Xu (PLoS ONE, 2025)
Objective Cardiopulmonary dysfunction in burn patients is typically caused by both the burn injury and smoke inhalation. Normally presenting with symptoms such as dyspnea, decreased exercise tolerance, decreased maximal heart rate, and decreased arterial oxygen saturation. It has been demonstrated that physical activity helps to increase cardiorespiratory fitness. The goal of this study was to determine whether physical activity can provide additional benefits to the recovery of cardiorespiratory fitness in burn patients by examining research on the topic of physical activity’s ability to enhance cardiorespiratory fitness in burn patients. Methods The electronic databases Web of Science, PubMed, Embase, and Cochrane Library were searched from their inception until August 30, 2024. To contrast the efficacy of conventional rehabilitation with the benefits of physical exercise in conjunction with it. Revman 5.4 software was employed to conduct a meta-analysis, with peak oxygen consumption serving as the primary outcome indicator and the 6-minute walking test (6MWT), forced vital capacity (FVC)%, forced expiratory volume in the first second (FEV1)%, max heart rate (HRmax), and resting heart rate (RHR) serving as secondary outcome indicators. The literature’s risk of bias was evaluated using the Cochrane Collaboration tool. Results A total of 13 studies were incorporated into the meta-analysis, which involved 530 patients. The study results demonstrated that physical exercise combined with conventional rehabilitation significantly improved VO2Peak (MD = 4.91, 95% CI: 3.52–6.29, P < 0.001), 6MWT (MD = 37.11, 95% CI: 11.72–62.51, P = 0.004), FVC% (MD = 6.54, 95% CI: 4.9–8.17, P < 0.001), and FEV1% (MD = 8.27, 95% CI: 7.39–9.14, P < 0.001) in burn patients compared to conventional rehabilitation. Furthermore, there was no significant difference in the change in resting heart rate (RHR) (MD = 2.04, 95% CI: −2.71–6.78; P = 0.40) between the physical activity group and the control group, but there was a significant difference in the change in maximum heart rate (HR-max) (MD = 6.27, 95% CI: 1.75–10.97, P = 0.007). The results of the subgroup analysis of VO2peak indicate that resistance training combined with aerobic exercise (MD = 5.47, 95% CI: 4.81–6.13, P < 0.001) is more effective than aerobic exercise alone. In terms of single exercise duration, exercise lasting longer than 60 minutes (MD = 6.32, 95% CI: 4.49–6.16, P < 0.001) is more effective than exercise lasting less than 60 minutes. The improvement effects in adult burn patients (MD = 6.09, 95% CI: 3.7–8.48, P < 0.001) were superior to those in pediatric burn patients. The improvement effects in severe burn patients (MD = 5.66, 95% CI: 4.2–7.12, P < 0.001) were superior to those in moderate burn patients. Conclusions Our study results indicate that physical exercise, when combined with conventional rehabilitation, is more effective than conventional rehabilitation alone in improving cardiorespiratory fitness in burn patients. This is demonstrated by improvements in aerobic capacity, exercise performance, and respiratory function. The most effective approach may involve combining prolonged resistance with aerobic exercise. The certainty of the evidence assessed according to the GRADE guidelines was moderate and very low, with key factors such as publication bias, imprecision, and inconsistency leading to its downgrading.